Enhancing MSMES Performance Through Digital Leadership and Organizational Citizenship Behaviour: Does Digital Transformation Matter? - Rizqon Jamil Farhas; Wahyu Febri Ramadhan Sudirman; M Abdi Dzil Ikhram; Bord Nandre Aprila (CV. Sakura Digital Nusantara, 2026)
Purpose – This study investigates the effects of Digital Leadership and Organizational Citizenship Behavior (OCB) on MSME performance and examines the mediating role of Digital Transformation from the perspective of Dynamic Capability Theory. Design/Methodology/Approach – A quantitative explanatory study with a cross-sectional design was conducted involving 220 MSME owners in Kampar Regency, Riau Province, Indonesia, using a census sampling approach. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The results show that Digital Leadership and OCB significantly promote Digital Transformation. Digital Leadership and Digital Transformation positively affect MSME performance, whereas OCB has no direct effect on performance but exerts a significant indirect effect through Digital Transformation. These findings highlight Digital Transformation as a strategic capability that translates leadership quality and positive organizational behavior into improved business performance. Originality/Value – This study extends Dynamic Capability Theory by integrating Digital Leadership, OCB, and Digital Transformation into a unified framework for explaining MSME performance. The findings demonstrate that successful digital transformation depends not only on technology adoption but also on effective leadership and organizational commitment, providing practical implications for MSME managers and policymakers.